Antimicrobial activity of Davilla elliptica St. Hill (Dilleniaceae) - Michelin, D. C. [UNESP]; Iha, S. M. [UNESP]; Rinaldo, D. [UNESP]; Sannomiya, M. [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Vilegas, Wagner [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Sociedade Brasileira de Farmacognosia, 2005)
Davilla elliptica St. Hill (lixinha), family Dilleniaceae, is commonly used in the Brazilian folk medicine as purgative and stimulant. This work evaluated the antimicrobial activity of the methanol and chloroform extracts of the leaves and barks of D. elliptica using the disc-diffusion method. The results obtained showed that the methanolic extracts of the leaves and barks presented antimicrobial activity against the tested microorganisms.
Keywords: Davilla elliptica; Dilleniaceae; antimicrobial activity